ANALISIS PENGARUH FAKTOR LINGKUNGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS PEGAWAI: STUDI PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN GOWA - Salsi, Marinda (Universitas Teuku Umar, 2024)
This study aims to (1) To determine the influence of the work environment on employee performance at the Gowa Regency Trade and Industry Office (2) To determine the influence of work stress on employee performance at the Gowa Regency Trade and Industry Office. This sample consisted of 34 respondents. The type of data used in this study is quantitative data. Data collection was carried out by observation and distribution of questionnaires. Based on the results of data analysis using the application (SPSS) version 26, the results of the multiple linear regression test indicate that the work environment and work stress have a positive and significant effect on employee performance, with regression coefficient values of 0.401 and 0.479, respectively. The t-test shows significance (<0.05) for both variables, and the F-test shows a significant value (0.000). The R² value of 0.492 indicates that 49.2% of the variation in employee performance is explained by these two variables.Keywords : Work Environment, Work Stress and Employee Performance